The role of naturally occurring alleles of rpoS in Escherichia coli - Gyewu, Daniel (My University, 2008)
Sigma S (RpoS), encoded by rpoS, is a subunit of RNA polymerase holoenzyme that controls the expression of many genes in stationary phase of various gram negative bacteria. Escherichia coli expresses these genes to withstand environmental stress and nutrient starvation. Several naturally occurring mutant alleles of the gene have been reported and indicate key differences from laboratory strains. We sought to explore the role of natural alleles of the rpoS gene (from non- K12 strains) and thus the sigma subunit relative to the K12 allele. To study the effect of the rpoS polymorphism on gene expression ofRpoS regulon members, rpoS alleles from ECOR- 21, ECOR-28, ECOR-37 and ECOR-40 as well as MG1655 were cloned into the same background, MG1655 ΔrpoS:cat osmY-lacZ. Sequence analysis showed rpoS alleles from all the natural strains tested were different from MG1655 and each other. The strain with rpoS allele from ECOR-28 had increased expression of osmY and katE similar to MG1655. In contrast, rpoS allele from ECOR- 37 showed low expression of osmYbut not as low as ECOR-21 and ECOR-40 which had expression similar to the rpoS mutant. Not surprisingly, recombinant strains with rpoS alleles from ECOR-21, ECOR-37 and ECOR-40 showed no expression of katE (HPII). These suggest that RpoS in ECOR-28 has high activity similar to wildtype K12 strain while RpoS in ECOR-21, ECOR-37 and ECOR-40 has very low or no activity. We conclude that natural E. coli strains have polymorphism in their rpoS ORF which cause variation in the regulatory activities of RpoS on its regulon.
Keywords: alleles; rpoS; Escherichia coli; RNA; polymerase holoenzyme